Augmented reality in language learning: A state‐of‐the‐art review of 2014–2019 - Parmaxi, Antigoni; Demetriou, Alan A. (Journal of computer assisted learning, 2020)
This systematic review study synthesizes research findings pertaining to the use of augmented reality (AR) in language learning. Published research from 2014 to 2019 has been explored and specific inclusion and exclusion criteria have been applied resulting in 54 relevant publications. Our findings determined: (a) devices and software employed for mastering AR; languages and contexts in which AR had been applied; theoretical perspectives adopted for guiding the use of AR; the number of participants in AR activities and benefits from using AR as an educational tool in the language classroom; (b) alignment of the affordances of Augmented Reality with the KSAVE (Knowledge, Skills, Attitudes, Values, Ethics) 21st‐century skills framework; (c) future directions in AR research and practice. The main findings from this review demonstrate the popularity of mobile‐based AR for supporting vocabulary (23.9%), reading (12.7%), speaking (9.9%) writing (8.5%) or generic language skills (9.9%). Our findings also uncovered areas that merit future attention in the application of AR in language learning – for instance learning theories were not often considered in the implementation of AR. The study concludes with suggestions for future research especially in the areas of instructional design and user experience. Lay Description What is currently known about the subject matter Augmented reality (AR) has become an attractive trend in language learning. A number of reviews on AR in education have been conducted. The state of current research on AR in language learning lacks a comprehensive review. What their paper adds to this The paper presents a systematic review of relevant academic literature on AR in the field of language learning. The paper provides empirical evidence on the benefits of AR in language learning based on selected literature. The findings revealed that the majority of AR studies are mobile‐based. The main findings from this review demonstrate the popularity of mobile‐based AR for supporting vocabulary, reading, speaking writing or generic language skills. Future research in AR is needed with focus on instructional design and user experience. Implications of study findings for practitioners The systematic review adds to the body of knowledge a firm review of recent research findings in the field. Given the increased potential of AR, future research needs to focus on the development of under‐studied skills and competencies. AR is an optimal means to implement communicative language learning, through continuous dialogue about augmented information.